Stiffness Self‐Tuned Shape Memory Hydrogels for Embolization of Aneurysms. (7th April 2020) - Liu, Bo; Xu, Ziyang; Gao, Haijun; Fan, Chuanchuan; Ma, Guangshuo; Zhang, Dongfei; Xiao, Meng; Zhang, Bingjie; Yang, Yang; Cui, Chunyan; Wu, Tengling; Feng, Xuequan; et al.
Abstract: An aneurysm is a life‐threatening vascular disease. Embolization with shape memory (SM) hydrogel coils is promising for the treatment of the intractable aneurysms. However, single temperature‐triggered SM is softened in a catheter, and delivery of multiple coils is required, which may clog the catheter and complicate operation procedure. Here, a radiopaque temperature/pH dual responsive shape memory hydrogel with self‐tuned stiffness is fabricated by copolymerizing acrylonitrile (AN, dipole–dipole interaction monomer), N ‐acryloyl 2‐glycine (ACG, pH‐sensitive H‐bonding monomer), and polyethylene glycol diacrylate. Under slightly acidic conditions without eliciting cytotoxicity, additional supramolecular PACG hydrogen bonds combined with cyano dipole–dipole pairings contribute to the body temperature‐triggered SM effect with an unprecedented high 430 MPa (10 °C) and 16 MPa (37 °C) Young's modulus. A carotid aneurysm is created in a dog to test the embolization of this SM hydrogel. At 37 °C, the hydrogel's high stiffness ensures its smooth delivery through a catheter. After being transported into the aneurysm sac, secondary swelling occurs concurrent with appropriate decrease of stiffness upon contacting neutral blood, thus enhancing the packing density and reducing recanalization rate and delivery times. This stiffness adaptive SM hydrogel holds its great potential as permanent embolic agents for treating a variety of aneurysms. Abstract : A stiffness self‐tuned shape memory hydrogel reinforced with dipole–dipole interactions and pH‐responsive supramolecular hydrogen bonds embolizes carotid aneurysms in a dog, successfully addressing transluminal delivery difficulty through the confined space of a microcatheter, and reducing the recanalization rate and delivery times by actively adjusting its modulus and swelling behavior in response to the microenvironment temperature and pH.